Sozialismus und Frauenfrage - Zepler, Wally, Frau, 1865- (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1919)
This analysis of the connections between socialism and women includes essays by Zepler, as well as by Hedwig Dohm, Edmund Fischer, Oda Olberg, and Dr. Hope Bridges Adams-Lehmann.